2015
DOI: 10.7899/jce-14-37
|View full text |Cite
|
Sign up to set email alerts
|

Reassessing the educational environment among undergraduate students in a chiropractic training institution: A study over time

Abstract: Objective: The aim of the study was twofold: (1) to compare the perceived educational environment at 2 points in time and (2) to longitudinally examine potential changes in perceptions of the educational environment over time. Methods: The validated Dundee Ready Educational Environment Measure (DREEM), a 50-item, self-administered Likert-type inventory, was used in this prospective study. Employing convenience sampling, undergraduate chiropractic students were investigated at 2 points in time: 2009 (n ¼ 124) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 82 publications
2
17
1
1
Order By: Relevance
“…Integration at the organizational level is exemplified by a study in which chiropractic students were interviewed at 3-year intervals about their views on what constitutes a good educational environment (Palmgren, Sundberg, & Laksov, 2015). The study found that the importance of different aspects of the educational environment changed over time, but both at the beginning and towards the end of their education, participation in a community was central for students' learning experience.…”
Section: Organizational Level: Adaptation and Level Of Individualitymentioning
confidence: 99%
“…Integration at the organizational level is exemplified by a study in which chiropractic students were interviewed at 3-year intervals about their views on what constitutes a good educational environment (Palmgren, Sundberg, & Laksov, 2015). The study found that the importance of different aspects of the educational environment changed over time, but both at the beginning and towards the end of their education, participation in a community was central for students' learning experience.…”
Section: Organizational Level: Adaptation and Level Of Individualitymentioning
confidence: 99%
“…4,13 In the present study, teachers did, in part, acknowledge these aspects as challenges for their respective programs. However, they also rejected some of the students' statements, suggesting that students perhaps did not fully understand the need for factual knowledge and did not understand that facts can be clinically contextualized and that this ''aha!''…”
Section: Discussionmentioning
confidence: 89%
“…4,12,13 These empirical findings suggest that both these groups have similar judgments of the environment and perceive it as very good, but some aspects of the environment recorded low scores in both the cross-sectional and the longitudinal data, such as limited support for stressed students, teachers being authoritarian, and an overemphasis on factual learning. Moreover, even though a handful of surveybased investigations, apart from ours, have been conducted on these student populations, 4,[13][14][15] to our knowledge there are no existing qualitative explorations of how teachers in these contexts experience the educational environment. Additionally, we have previously qualitatively explored chiropractic students and found that early in the training, the educational environment was experienced as part of a vocational community and the scaffolding of institutional relationships.…”
Section: Introductionmentioning
confidence: 78%
“…Deriving a percentage score from a rating scale is a common method for presenting EEM scores. 4,5,[19][20][21][22][23][24] The wider and consistent margins inherent in a 0-100 scale facilitate comparison between different measures or the same measure applied at a different time or place. A requirement for converting from a rating scale to a percentage score is factoring a zero point into the conversion if the lowest value in the original scale is not zero.…”
Section: Conversion To Percentage Scorementioning
confidence: 99%
“…Potential applications of the MATE in the context of anesthesiology training are numerous. In other settings, EEMs have been used to evaluate interventions designed to improve teaching and learning, 25 monitor the impact of curricular change, [26][27][28] longitudinal changes over time and between cohorts, 23 and differences in training locations. 24 In a recent review of a generic postgraduate training EEM, 8/9 studies reported significant differences in overall EEM scores for rural vs urban training locations.…”
Section: Utilitymentioning
confidence: 99%